Unveiling the Burden of Pruritus: Its Prevalence and Impact on Sleep Quality in Hemodialysis Patients in Somalia - Jeele MOO; Adam AM; Addow ROB (International Journal of General Medicine)
Mohamed Osman Omar Jeele,1 Abdisamad Mohamed Adam,1 Rukia Omar Barei Addow2 1Department of Internal Medicine, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, Somalia; 2Department of Public Health, Horseed International University, Mogadishu, SomaliaCorrespondence: Mohamed Osman Omar Jeele, Department of Internal Medicine, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, Somalia, Tel +252615775226, Email drjeele@gmail.comIntroduction: Despite its ubiquity, pruritus is frequently underreported and inadequately handled in healthcare settings, such as Somalia. This study aimed to investigate the prevalence of pruritus and their impact on sleep quality among hemodialysis patients in Somalia.Methods and Materials: Between February and April 2024, a cross-sectional study was done at the Mogadishu Somali Turkish Training and Research Hospital. Two hundred and ninety-nine routine hemodialysis patients had participated. The 12-item Pruritus Severity Scale (12-PSS) was used to assess pruritus severity, and the Pittsburgh Sleep Quality Index was used for sleep quality. Descriptive tests and logistic regressions were applied for analysis.Results: The mean age of participants was 56.65 ± 12, ranging from 19 to 81 years. 76.9% of patients reported pruritus, with 68% moderate and 24.3% severe. The mean  12-PSS score was 10.32 ± 2.16. Pruritus was associated with comorbidities (OR: 2.791, P < 0.001) and duration of hemodialysis (OR: 0.609, P < 0.003). The average PSQI score was 8.69 ± 5.8, and 61.9% of patients were classified as bad sleepers. Poor sleep quality was substantially associated with pruritus (P < 0.001). We found R2 =  0.10, F (5,293) =  4.38, p < 0.001, in the multiple regression between pruritus and age, sex, duration of hemodialysis and sessions of hemodialysis per week. Also, age group, sex, presence of comorbidities, duration of hemodialysis, sessions of hemodialysis per week, and pruritus have shown R2 =  0.34, F (6,292) =  26, p < 0.001.Conclusion: Pruritus is associated with poor sleep and patients who were living with co-morbidities and patients who were going to hemodialysis for a long time tend to develop pruritus. Effective pruritus management is critical for better patient outcomes and quality of life.Keywords: hemodialysis, pruritus, sleep quality, chronic kidney disease, Somalia